Patterns of parental relatedness and pup survival in the grey seal (Halichoerus grypus). - Bean, K; Amos, W; Pomeroy, P; Twiss, S; Coulson, T; Boyd, I (2004)
Levels of parental relatedness can affect offspring survival and susceptibility to disease. We investigated parental relatedness of live and dead Halichoerus grypus pups between and within island populations and between possible causes of mortality. Nine microsatellites were used to calculate internal relatedness (IR) and standardized mean d2. We find that pups with higher than average levels of IR have significantly lower survival and that this varied between island populations and that certain loci contributed to the effect more than others. Although, there were no significant differences between causes of mortality, peritonitis, infection and stillborn had the highest levels of IR. These results provide evidence that parental relatedness is an important determinant of pre-weaning pup survival in the grey seal and that this may vary with cause of mortality given a larger sample size.